Assessing the Use of Cohesive Devices in Reading Texts of English Textbook - Alifia Junita Cendraa Sari; Januarius Mujiyanto; Dwi Rukmini (Universitas Negeri Semarang, 2022)
The present study began with wide use of a textbook entitled